Is Malaysian Islamic home financing bay’ bithaman al-ajil (‘BBA’) compatible with Islamic law? A critical examination on the issue of ‘beneficial ownership’ - Md Dahlan, Nuarrual Hilal; Mohd Noor, Fauziah; Shuib, Mohd Sollehudin (2016)
Islamic Banking has been established since 1980s in Malaysia.It was initially commenced with the incorporation of Bank Islam Malaysia Berhad (‘BIMB’) in 1983. Until today, Islamic Banking has robustly developed in Malaysia.Various Islamic Banking products have been introduced and practised in Malaysia.Among the products are: Bay’ Bithaman al-Ajil (BBA), Musharakah al-Mutanaqisah (MM), Commodity Murabahah and Ijarah.Nonetheless, there are many issues in these products.One of the issues is the issue of beneficial ownership in BBA.It is evident that, the application of BBA is proven to be defective and contains many flaws, if involves pending completion housing development projects.This paper discusses this issue through the shariah doctrinal and qualitative case study research methodologies.The outcome of this paper will help the Islamic banking industry in dealing with issues arising from ‘beneficial ownership’ in transaction involving houses pending completion in Malaysia.